2017
DOI: 10.3390/electronics6030056
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Based Nanomechanical Sensor: Theoretical Analysis of Mechanical and Vibrational Properties

Abstract: This paper reviews the recent research of carbon nanotubes (CNTs) used as nanomechanical sensing elements based mainly on theoretical models. CNTs have demonstrated considerable potential as nanomechanical mass sensor and atomic force microscope (AFM) tips. The mechanical and vibrational characteristics of CNTs are introduced to the readers. The effects of main parameters of CNTs, such as dimensions, layer number, and boundary conditions on the performance characteristics are investigated and discussed. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…We summarize some of the representative works with respect to CNTs-based nano-mass sensor adopting FEM [ 126 , 127 , 128 , 129 , 130 , 131 , 132 ], Euler–Bernoulli beam theory (EBT) [ 127 , 129 , 131 , 135 , 138 , 140 ], nonlocal EBT [ 133 , 134 , 136 , 139 , 142 , 143 , 144 ], Timoshenko beam theory (TBT) [ 141 ], nonlocal TBT [ 137 ] for studying CNTs-based nano-mass sensors as shown in Table 1 , from which we can see that though the work considering thermal and nonlocal effects could make sensitivity to atom mass of 6.65 × 10 −24 g and 0.218 × 10 −24 g under special thermal conditions [ 143 , 144 ], most of the works indicated that the CNTs-based nano-mass sensor could detect tiny mass larger than 10 −21 g. Moreover, detail of CNTs-based nano-mass sensor can be also found in some previous review works [ 18 , 145 ].…”
Section: Nano-mass Sensormentioning
confidence: 99%
“…We summarize some of the representative works with respect to CNTs-based nano-mass sensor adopting FEM [ 126 , 127 , 128 , 129 , 130 , 131 , 132 ], Euler–Bernoulli beam theory (EBT) [ 127 , 129 , 131 , 135 , 138 , 140 ], nonlocal EBT [ 133 , 134 , 136 , 139 , 142 , 143 , 144 ], Timoshenko beam theory (TBT) [ 141 ], nonlocal TBT [ 137 ] for studying CNTs-based nano-mass sensors as shown in Table 1 , from which we can see that though the work considering thermal and nonlocal effects could make sensitivity to atom mass of 6.65 × 10 −24 g and 0.218 × 10 −24 g under special thermal conditions [ 143 , 144 ], most of the works indicated that the CNTs-based nano-mass sensor could detect tiny mass larger than 10 −21 g. Moreover, detail of CNTs-based nano-mass sensor can be also found in some previous review works [ 18 , 145 ].…”
Section: Nano-mass Sensormentioning
confidence: 99%
“…Recently, Carbon Nanotubes (CNTs) have come to the fore as most promising materials and are being considered for a wide variety of applications ranging from large-scale structure to nanometer-scale electronics because of their superior mechanical and physical properties [32,33]. CNTs were discovered accidentally by Japanese physicist S. lijima [34] in 1991 when performing experiments on carbonium. CNTs are basically nano-scaled tubes formed by the rolled sheets of graphite and possess high tensile strength, high electrical conductivity and excellent chemical stability [35].…”
Section: A Brief On Carbon Nanotube Field Effect Transistors (Cntfets)mentioning
confidence: 99%
“…10, pp: ------ The arrow in the center of the molecule indicates the direction of the dipole moment of the active mode of vibration in the infrared spectrum]. And similarly to the single wall carbon nanotubes (SWCNs) [18,[23][24][25][26], the calculations of electronic charge for [7] Science, 2019, Vol. 60, No.…”
Section: Kubbamentioning
confidence: 99%